The Effect of Luminous Intensity, Humidity, and Temperature on The Output Voltage of Solar Panels - Damarwan, Eko Swi; Hakim, Muhammad Luthfi; Wardhana, Alex Sandria Jaya; Budiastuti, Pramudita (Jurnal Edukasi Elektro, 2023)
Solar Power Plant is a power plant by utilizing sunlight. In this study, the focus is on the use of off-grid solar power systems. The purpose of this study is to determine the effect of luminous intensity, humidity, and temperature on the output voltage of a solar power plant. The research method used is experimental. The maximum output voltage of the solar panel is 19.2 V obtained at 01.00 pm. During these conditions, the luminous intensity value is 121000 lux at an air humidity of 52.4% with a temperature of 40.50C. The results showed that (1) the greater the luminous intensity, the greater the output voltage of the solar panel. (2) If the greater the humidity, the smaller the output voltage of the solar panel. (3) If the greater the temperature, the greater the output voltage of the solar panel.